Funded and Unfunded Pension Schemes: Risk, Return and Welfare - David K. Miles (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper uses stochastic simulations on calibrated models to assess the optimal degree of reliance on fun ded pensions and on a particular type of unfunded (PAYG) pension. Surprisingly little is known about the optimal split between funded and unfunded systems when there are sources of uninsurable risk that are allocated in different ways by different types of pension system. This paper calculates the expected welfare of agents in differenteconomies where in the steady state the importance of PAYG pensions differs. We estimate how the optimal level of unfunded, state pensions depends on rate of return and income risks and also upon the actuarial fairness of annuity contracts.
Keywords: D91; G22; H55; J14; 330; Pensions; annuities; risk-sharing